2021
DOI: 10.1186/s13017-021-00360-5
|View full text |Cite
|
Sign up to set email alerts
|

Timing of early laparoscopic cholecystectomy for acute calculous cholecystitis: a meta-analysis of randomized clinical trials

Abstract: Background Early cholecystectomy for acute cholecystitis has proved to reduce hospital length of stay but with no benefit in morbidity when compared to delayed surgery. However, in the literature, early timing refers to cholecystectomy performed up to 96 h of admission or up to 1 week of the onset of symptoms. Considering the natural history of acute cholecystitis, the analysis based on such a range of early timings may have missed a potential advantage that could be hypothesized with an early … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
22
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(26 citation statements)
references
References 40 publications
1
22
0
3
Order By: Relevance
“…Importantly, this was not reflected in the complication severity as defined by Clavien-Dindo classification scores, mortality rates or re-operation rates. These findings are in harmony with the outcome of a 2021 meta-analysis by Borzellino et al showing that LC within 72 h of symptoms significantly reduces postoperative complications when compared to delayed cholecystectomy [21]. Conversely, Menahem et al concluded in a 2015 meta-analysis that while ELC and DLC are equivalent in terms of overall morbidity, major bile duct injury and mortality, ELC was significantly associated with postoperative bile leaks and a higher incidence of intraoperative insertion of drainage tubes [22].…”
Section: Perioperative Complicationssupporting
confidence: 53%
“…Importantly, this was not reflected in the complication severity as defined by Clavien-Dindo classification scores, mortality rates or re-operation rates. These findings are in harmony with the outcome of a 2021 meta-analysis by Borzellino et al showing that LC within 72 h of symptoms significantly reduces postoperative complications when compared to delayed cholecystectomy [21]. Conversely, Menahem et al concluded in a 2015 meta-analysis that while ELC and DLC are equivalent in terms of overall morbidity, major bile duct injury and mortality, ELC was significantly associated with postoperative bile leaks and a higher incidence of intraoperative insertion of drainage tubes [22].…”
Section: Perioperative Complicationssupporting
confidence: 53%
“…In contrast, elective surgery allows maturation of the associated inflammation, leading to the organization of dense adhesions and scarring of the gallbladder 34 . Dissection of the gallbladder under chronic inflammatory conditions is often more difficult and can lead to more postoperative complications 35 . To date, emergency LC has not resulted in poorer outcomes than elective LC for the management of acute cholecystitis 36 .…”
Section: Discussionmentioning
confidence: 99%
“… 34 Dissection of the gallbladder under chronic inflammatory conditions is often more difficult and can lead to more postoperative complications. 35 To date, emergency LC has not resulted in poorer outcomes than elective LC for the management of acute cholecystitis. 36 Evaluating these outcomes more closely in the obese population is important as obesity was previously identified as a risk factor for conversion to open surgery in those undergoing emergency LC.…”
Section: Discussionmentioning
confidence: 99%
“…50 Recent meta-analyses also suggested ELC as safe and effective against DLC for acute cholecystitis within 7 days from presentation 51 ; also, ELC should be preferred to DLC when feasible within 72 hours of the onset of symptoms. 52 In 2020, the World Society of Emergency Surgery recommended that ELC should be the standard of care whenever possible. 53 Previous Randomised control trials have reported quality improvements and cost savings through same-day surgery (ELC) over preoperative admission.…”
Section: Discussionmentioning
confidence: 99%
“…A systematic review of meta-analyses by Song et al suggested ELC as the standard treatment option and indicated a non-significant difference in mortality and complications, with a significant reduction in hospitalisation and improvement in quality of life when compared with DLC 50. Recent meta-analyses also suggested ELC as safe and effective against DLC for acute cholecystitis within 7 days from presentation51; also, ELC should be preferred to DLC when feasible within 72 hours of the onset of symptoms 52. In 2020, the World Society of Emergency Surgery recommended that ELC should be the standard of care whenever possible 53…”
Section: Discussionmentioning
confidence: 99%